Ofdm system cyclic prefix characteristic analaysis for wimax technology - Mohammed Ahmed, Adeb Ali (2015)
In the modern world, Wireless Communication System are involved in every part of life. Worldwide Interoperability for Microwave Access (WIMAX) system based on Orthogonal Frequency Division Multiplexing (OFDM) with different adaptive modulation techniques is currently the topic of discussion.WIMAX is the next generation of broadband wireless technology which offers a greater range and bandwidth compared to the other available broadband wireless access technologies such as Wireless Fidelity (Wi- Fi) and Ultra Wideband (UWB) Family of standards. This research is focus on Orthogonal Frequency Division Multiplexing (OFDM) using adaptive modulation technique on the physical layer of WIMAX using the concept of cyclic prefix that adds additional bits at the transmitter end. The purpose of the cyclic prefix is to minimize the inter symbol interference and to improve the bit error rate. The MATLAB software is used to develop the OFDM model with cyclic prefix and analysis the performance of the WIMAX system. The performance of this system is compared between the models with one cyclic prefix, two cyclic prefix and without cyclic prefixed. The performance analysis is based on the Bit Error Rate (BER), Signal to Noise Ratio (SNR) and probability of error. The simulation results shows that modulation BPSK and QPSK have the low bit error rate while 64-QAM has the highest bit error rate equal to